Stan badań nad klasztorem kanoników regularnych w Żaganiu w średniowieczu = The state of research on the monastery of regular canons in Żagań in the middle ages - Witczak, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article deals with the state of the research on the monastery of the canons regular in Żagań. The monastery was founded in the 13th century by Henryk I ?the Bearded? Prince of Silesia and established in Nowogród Bobrzański.
Keywords: Żagań - Klasztor Augustianów - historia; Żagań; kanonicy regularni; średniowiecze; opactwo; badania; regular canons; Middle Ages; abbey; researches